1998
DOI: 10.1111/j.1572-0241.1998.452_a.x
|View full text |Cite
|
Sign up to set email alerts
|

Has the Impact of Helicobacter pylori Therapy on Ulcer Recurrence in the United States Been Overstated?

Abstract: Results of North American studies of highest methodological quality confirm that H. pylori eradication markedly decreases ulcer recurrence. Nevertheless, 20% of patients in these studies had ulcer recurrence within 6 months, despite successful cure of infection and no reported use of NSAIDs. Non-H. pylori, non-NSAID ulcers may be more common in the U.S. than previously believed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
83
1
1

Year Published

1998
1998
2018
2018

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 100 publications
(85 citation statements)
references
References 20 publications
0
83
1
1
Order By: Relevance
“…GI-drug costs ›42 ›18 (p = .02 a ) PPI costs ›11 ›12 (p = .84) % on GI-drugs (PPI) 100% (21%) 37% (43%) Non-Ulcer (n = 67) GI-drug costs ›38 ›38 (p = .96) PPI costs ›18 ›32 (p = .02 a ) % on GI-drugs (PPI) 66% (32%) 33% (68%) Non-Ulcer chronic (n = 44) GI-drug costs ›58 ›29 (p = .008 a ) PPI costs ›27 ›23 (p = .58) % on GI-drugs (PPI) 100% (32%) 41% (67%) All (n = 102) GI-drug costs ›33 ›34 (p = .82) PPI costs ›14 ›28 (p = .005 a ) % on GI-drugs (PPI) 61% (29%) 33% (59%) All chronic (n = 63) GI-drug costs ›53 ›26 (p = .0007 a ) PPI costs ›22 ›20 (p = .62) % on GI-drugs (PPI) 100% (29%) 40% (60%) a significant on a 95% CI-level. et al [15] found that 20% of ulcer recurrence was neither NSAID nor H. pylori induced. The findings of Laine et al are not necessarily true for the Netherlands, nevertheless they could explain some of the post eradication users.…”
Section: Discussionmentioning
confidence: 98%
“…GI-drug costs ›42 ›18 (p = .02 a ) PPI costs ›11 ›12 (p = .84) % on GI-drugs (PPI) 100% (21%) 37% (43%) Non-Ulcer (n = 67) GI-drug costs ›38 ›38 (p = .96) PPI costs ›18 ›32 (p = .02 a ) % on GI-drugs (PPI) 66% (32%) 33% (68%) Non-Ulcer chronic (n = 44) GI-drug costs ›58 ›29 (p = .008 a ) PPI costs ›27 ›23 (p = .58) % on GI-drugs (PPI) 100% (32%) 41% (67%) All (n = 102) GI-drug costs ›33 ›34 (p = .82) PPI costs ›14 ›28 (p = .005 a ) % on GI-drugs (PPI) 61% (29%) 33% (59%) All chronic (n = 63) GI-drug costs ›53 ›26 (p = .0007 a ) PPI costs ›22 ›20 (p = .62) % on GI-drugs (PPI) 100% (29%) 40% (60%) a significant on a 95% CI-level. et al [15] found that 20% of ulcer recurrence was neither NSAID nor H. pylori induced. The findings of Laine et al are not necessarily true for the Netherlands, nevertheless they could explain some of the post eradication users.…”
Section: Discussionmentioning
confidence: 98%
“…Recently, it has been reported that the duodenal ulcer recurrence rate for patients with H. pylori eradication after therapy may be higher within the USA (» 20%). 71 Geographic variations in the duodenal ulcer recurrence rates may very well Figure 4. Overall 12-month duodenal ulcer recurrence rates post-therapy, combining treatments, from controlled and uncontrolled clinical studies for patients with H. pylori eradication (H. pylori Ave) and those remaining H. pylori positive (H. pylori +ve) at least 4 weeks after therapy, categorized by whether eradication was achieved using omeprazole and antimicrobial agents or bismuth and antimicrobial agents.…”
Section: Discussionmentioning
confidence: 99%
“…Those receiving long-term treatment with H 2 -receptor antagonists have recurrence rates of 30%/year. In contrast, the recurrence rate within 1 year after H. pylori eradication therapy is less than 20%, which has been shown in a number of studies, including a meta-analysis of double-blinded, randomized trials of duodenal ulcer patients with H. pylori [22]. Similar trials show that H. pylori eradication reduces the recurrence rate for gastric ulcers [23].…”
Section: Gastric Ulcer and Duodenal Ulcermentioning
confidence: 99%